Estimates of Effective Rates of Protection for United States Industries in 1967 - Witthans, Fred (The Review of Economics and Statistics, 1973)
T-HE theory of effective protection was initially developed under the assumption of fixed input coefficients.' Later, the theory was expanded to allow for factor substitution.2 In the process, the concept of effective protection has been changed from defining it as the percentage change in value added per unit of output to defining it as the percentage change in the price of the value-added product. The original definition is: Iv'-v fi = v